Draft Sixth Five Year Plan 1980-85 Government of India Planning Commission - Planning Commission (Planning Commission, 1980)
Soon after its reconstitution in April, 1980, the Planning Commission started work on the Sixth Five Year Plan 1980-85. A number of Working groups were set up to do the necessary preparatory work and consultations were held with the Central Ministries and the Consultative Committee of Members of Parliament on Planning.
Government of India Planning Commission
Government of India Planning Commission